Dual-targeted N-PMIplus@CA nanoplatform for concurrent MDM2 and β-catenin inhibition in p53 wild-type lung adenocarcinoma - Ni Zhao; Weiming You; Xiaoqiang Zheng; Jin Yan; Peili Wang; Yu Yao; Wangxiao He; Tianya Liu (Materials Today Bio, 2025)
Lung adenocarcinoma (LUAD) harboring wild-type p53 remains therapeutically challenging because of the oncogenic MDM2-driven suppression of p53 activity and compensatory activation of Wnt/β-catenin signaling. Here, we report a self-assembled nanoparticle system (N-PMIplus@CA) enabling simultaneous inhibition of both MDM2 and the Wnt/β-catenin pathway. We observed that concurrent activation of these two pathways is significantly correlated with poor clinical outcomes in patients with LUAD. N-PMIplus@CA efficiently accumulated in tumor tissues via enhanced permeability and retention (EPR) effects and macropinocytosis, delivering both an optimized MDM2-inhibitory peptide and a β-catenin antagonist (carnosic acid). The dual-inhibition strategy significantly restored p53 function, downregulated β-catenin signaling, suppressed tumor proliferation, and promoted apoptosis in LUAD cell lines and murine models. Remarkably, treatment with N-PMIplus@CA yielded superior antitumor efficacy in subcutaneous and orthotopic LUAD models compared with monotherapy controls, without detectable systemic toxicity. The unified pharmacokinetic profile achieved by coencapsulation ensured synchronized intracellular delivery and maximal synergistic effects at tumor sites. This nanomedicine approach effectively circumvents traditional dual-drug therapy limitations, such as differential metabolism and systemic adverse effects. Collectively, our findings highlight N-PMIplus@CA as a promising clinical candidate that addresses a critical unmet need in p53 wild-type LUAD treatment, demonstrating strong translational potential and providing a paradigm for simultaneous targeting of multiple oncogenic pathways.